The Use of Race in US Admissions is Not Over, Unless We Let It - Muñiz, Raquel; Samayoa, Andrés (International Higher Education, 2024)
After Students for Fair Admissions v. Harvard (2023), people are likely to think race is scrubbed from college admissions processes. This interpretation is a misunderstanding of the new legal reality in the United States. We offer two sources of hope outlining the path forward for educational leaders, parents, and students.